ORANG ASING SEBAGAI SUBJEK HAK ATAS TANAH DI INDONESIA - FX. Sumarja (Masalah-Masalah Hukum, 2015)
This research aims at finding foreigners who may be the subject of Land Use Rights and Lease Rights for the building. The results of the study indicate: 1) Period, BAL-PP 41 of 1996, and the period of 2010 - now, foreigners who can be the subject of land rights are foreigners as the resident of Indonesia; 2) Period, PP 41 of 1996 - in 2010, foreigners who may be the subject of land rights was expanded into foreigners as both a resident of Indonesia and has a residence permit in Indonesia.